Epicardial high-resolution mapping of advanced interatrial block: Relating ECG, conduction abnormalities and excitation patterns - Ramdat Misier, Nawin L.; van Schie, Mathijs S.; Li, Chunsheng; Oei, Frans B. S.; van Schaagen, Frank R. N.; Knops, Paul; Taverne, Yannick J. H. J.; de Groot, Natasja M. S. (Frontiers in Cardiovascular Medicine, 2023)
Background Impairment of conduction across Bachmann’s Bundle (BB) may cause advanced interatrial block (a-IAB), which in turn is associated with development of atrial fibrillation. However, the exact relation between a complete transverse line of conduction block (CB) across BB and the presence of a-IAB has not been studied. Objective The aims of this study are to determine whether (1) a complete transversal line of CB across BB established by high resolution mapping correlates with a-IAB on the surface ECG, (2) conduction abnormalities at the right and left atria correlate with a-IAB, and (3) excitation patterns are associated with ECG characteristics of a-IAB. Methods We included 40 patients in whom epicardial mapping revealed a complete transverse line of CB across BB. Pre-operative ECGs and post-operative telemetry were assessed for the presence of (a) typical a-IAB and de novo early post-operative AF (EPOAF), respectively. Total atrial excitation time (TAET) and RA-LA delay were calculated. Entry site and trajectory of the main sinus rhythm wavefront at the pulmonary vein area (PVA) were assessed. Results Thirteen patients were classified as a-IAB (32.5%). In the entire atria and BB there were no differences in conduction disorders, though, patients with a-IAB had an increased TAET and longer RA-LA delay compared to patients without a-IAB (90.0 ± 21.9 ms vs. 74.9 ± 13.0 ms, p = 0.017; 160.0 ± 27.0 ms vs. 136.0 ± 24.1 ms, p = 0.012, respectively). Patients with typical a-IAB solely had caudocranial activation of the PVA, without additional cranial entry sites. Prevalence of de novo EPOAF was 69.2% and was similar between patients with and without a-IAB. Conclusion A transverse line of CB across BB partly explains the ECG characteristics of a-IAB. We found atrial excitation patterns underlying the ECG characteristics of both atypical and typical a-IAB. Regardless of the presence of a-IAB, the clinical impact of a complete transverse line of CB across BB was reflected by a high incidence of de novo EPOAF.